Praktek Dakwah Islam Pada Acara Sakinah Di Kilisuci Televisi (KSTV) Kediri - Mohammad Fikri Abdillah; Muhammad Diak Udin (Institut Agama Islam Tribakti (IAIT) Kediri, 2019)
Da'wah is an appeal or invitation made by someone to an individual or group to go to the path that Allah SWT desires to always surrender to Allah SWT for what is done every day. With the guidance of the Holy Qur'an that has been delivered by the Prophet Muhammad to all the people of the world. Many forms of da'wah can be done today, including preaching through mass media, including television media. The da'wah method carried out via mass media is almost the same as the da'wah process with others such as, Presentation or introduction to the problem, Explanation of the problem, question and answer and conclusions. In the method of da'wah it is also almost similar; namely Bil-Hikmah, Mauidzu Khasanah and Mujadalah. This research method uses a Qualitative Descriptive approach to the type of Field Research research. The results of this study in preaching are divided into three categories, namely; Sakinah Typing, Sakinah Live On Studio and Sakinah Live On The Road.